Effectiveness of Implementation of perma number 1 of 2015 concerning mobile courts (Case study at stabat religious court class IB) - Nadilla, Nadilla; Turnip, Ibnu Radwan Siddik (The International Journal of Politics and Sociology Research, 2025)
One of the most important things in a marriage practice is the registration of marriage and divorce. However, in reality, until now there are still people who do not carry out the administration of marriage and divorce registration, especially for people in remote areas. In fact, since 2013 the Supreme Court has implemented a mobile court to assist in this matter. This study aims to examine the effectiveness of the implementation of Supreme Court Regulation (PERMA) Number 1 of 2015 concerning mobile courts that occur at the Stabat Class 1B Religious Court. This study is an empirical legal study, with a sociological approach. Primary data sources were obtained from interviews with judges and parties who had been in court at the Religious Court. The data analysis used was qualitative analysis. The results of this study indicate that the administrative registration process and implementation of mobile courts are in accordance with the Supreme Court guidelines, with adequate facilities and services for the community. Mobile courts have proven effective in providing convenience, speed, low cost, and can be easily accessed by the community. However, increasing socialization and public understanding is still needed to maximize the benefits of this program. Because some respondents are not yet aware of the existence of mobile courts at the Stabat Religious Court and there are still underhand marriages in this area.